Development of 3D printed enzymatic biofuel cells for powering implantable biomedical devices - Jodeiri, Keyvan (2023)
The drive toward device miniaturisation in the field of enzyme-based bioelectronics established a need for multi-dimensional geometrically structured and highly effective microelectrodes, which are difficult to implement and manufacture in devices such as biofuel cells and sensors. Additive manufacturing coupled with electroless metal plating enables the production of three-dimensional (3D) conductive microarchitectures with high surface area for potential applications in such devices. However, interfacial delamination between the metal layer and the polymer structure is a major reliability concern, which results in device performance degradation and eventually device failure. This thesis demonstrates a method to produce a highly conductive and robust metal layer on a 3D printed polymer microstructure with strong adhesion by introducing an interfacial adhesion layer. Prior to 3D printing, multifunctional acrylate monomers with alkoxysilane (-Si-(OCH3)3) were synthesised via the Thiol-Michael addition reaction between pentaerythritol tetraacrylate (PETA) and 3-mercaptopropyltrimethoxysilane (MPTMS) with a 1:1 stoichiometric ratio. Alkoxysilane functionality remains intact during photopolymerisation in a projection micro-stereolithography (PµSLA) system and is utilised for the sol-gel reaction with MPTMS post-functionalisation of the 3D printed microstructure to build an interfacial adhesion layer. This functionalisation leads to the implementation of abundant thiol functional groups on the surface of the 3D printed microstructure, which can act as a strong binding site for gold during electroless plating to improve interfacial adhesion. The 3D conductive microelectrode prepared by this technique exhibited excellent conductivity of 2.2×107 S/m (53% of bulk gold) with strong adhesion between a gold layer and a polymer structure even after harsh sonication and adhesion tape test, which offers potential to build a robust 3D conductive microarchitecture for applications such as biosensors and biofuel cells. As a proof-of-concept, the microelectrode with gold-coated complex lattice geometry was employed as an enzymatic glucose anode, which showed a significant increase in the current output compared to the one in the simple cube form. As the first approach, glucose oxidase was used as an enzyme. To find the optimal protocol for the enzyme immobilisation, the enzyme was first immobilised on agarose to achieve the enzyme’s highest activity and stability. Then, this immobilisation protocol was applied to immobilise the enzyme on the gold electrode surface. Preliminary studies on the preparation of 3D gold diamond lattice microelectrode modified with cysteamine and glucose oxidase as a bioanode for single cell enzymatic biofuel cell (EFC) application were performed, which demonstrated high current density of 0.38 μA cm–2 at 0.35 V in glucose solutions. This method for fabrication of 3D conductive microelectrodes offers potential for several biological applications. Instead of using a thiol, the surface of the 3D-printed part can be functionalised with different other functional groups to create an appropriate surface for biomolecules and cell adhesion. Furthermore, the surface of thiol functionalised printed parts can be perfect for additional metal coatings, opening the door to the creation of highly efficient and customised implantable energy harvesters and biosensors.